Global Health Management in the Face of Emerging Pandemic Threats: Strategies, Challenges, and Opportunities for International Cooperation - Rajab, Wahyudin; Simon, John Christianto; Karningsih; Purwoko, Reza Yuridian; Limijadi, Edward Kurnia Setiawan (International Journal of Science and Society, 2024)
The global Pandemic that has emerged has led to big challenges for the world health system, showing limitations in infrastructure, response, and international coordination. Inequality in the distribution of health resources and access to maintenance, along with obstacles in communication and coordination of inter-country policies, shows the urgent need for evaluating and improving global health management strategies. This condition encourages the need for in-depth analysis of strategies that can be implemented in dealing with pandemics, including strengthening the health system and international cooperation. This study aims to identify and analyze various strategies in global health management to deal with pandemics that emerge, focusing on threats, challenges, and opportunities for international cooperation. This study uses a qualitative approach, relies on data from relevant studies and studies, and is followed by in-depth analysis to integrate findings. The results of this study indicate that the current global health system faces various challenges in dealing with the Pandemic, which include infrastructure readiness, the effectiveness of surveillance systems and early detection, as well as the need for stronger international cooperation. There are also challenges in coordinating between countries, political and economic influences, as well as obstacles in communication and dissemination of information. This study found that international cooperation, especially in research and medical development, sharing resources, and coordination by international organizations, is the key to tackling the Pandemic. Building the capacity of the health system in developing countries is also an important aspect of global strategy.